Do governing institutions affect foreign direct investment inflows? New evidence from emerging economies. (14th April 2009) - Wernick, David A.; Haar, Jerry; Singh, Shane
In recent years, Western governments and international financial institutions have urged developing countries to undertake a range of institutional reforms to attract greater investment flows and hasten socioeconomic development. But do countries with strong governing institutions and business-friendly policies truly attract proportionally more foreign direct investment (FDI) than those with weaker institutions and a less favourable policy mix? This study seeks to answer this question by examining data on FDI inflows for a sample of 64 emerging economies over time. The article begins by reviewing the literature on the determinants of FDI and recent empirical studies probing the connection between governing institutions and FDI flows to emerging economies. Based on this literature, several hypotheses are developed and tested with a new measure of institutional quality. The article concludes by interpreting the results of the statistical analyses, considering their policy implications, and offering directions for future research.